2022
DOI: 10.1039/d2ew00226d
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nanoparticles (both inorganic nanoparticles and nanoplastics) in drinking water treatment – coagulation/flocculation/sedimentation, and sand/granular activated carbon filtration

Abstract: Nanoparticles, such as metallic ones like Ag, Au and TiO2 as well as nanoplastics, are applied in or emitted by a wide variety of products or stem from degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…DWTPs are processes with multiple stages that provide safe drinking water for human consumption [83]. Conventional methods used to remove MPs/NPs from DWTPs include coagulation-flocculation-sedimentation (CFS), filtration [3,17,18,84], ozonation [19,85], and chlorination [85]. The treatment process in a DWTP influences the quality of the drinking water produced [72].…”
Section: Physicochemical Methods For Removal Of Micro-and Nanoplastic...mentioning
confidence: 99%
See 1 more Smart Citation
“…DWTPs are processes with multiple stages that provide safe drinking water for human consumption [83]. Conventional methods used to remove MPs/NPs from DWTPs include coagulation-flocculation-sedimentation (CFS), filtration [3,17,18,84], ozonation [19,85], and chlorination [85]. The treatment process in a DWTP influences the quality of the drinking water produced [72].…”
Section: Physicochemical Methods For Removal Of Micro-and Nanoplastic...mentioning
confidence: 99%
“…Another study on the removal of NPs from DWTP by using CFS and sand/GAC filtration revealed a difference in the NP removal mechanism between those two techniques, NPs of 200 nm being more efficiently removed by CFS, while some smaller NPs (50 nm) were better removed by GAC filtration [84].…”
Section: Adsorptionmentioning
confidence: 99%
“…The extensive of nanotechnology across industrial, agricultural and medical applications leads to increase their emissions into the environment, especially water [ [1] , [2] , [3] , [4] , [5] ]. Engineered nanoparticles can discharge into wastewater during their use and disposal.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these convenient features, the application of nanometric TiO 2 is limited by the easy agglomeration of its NPs [ 8 , 9 ], the transformation of its crystalline phases [ 10 , 11 ], a reduction in the surface area after heat treatment [ 8 , 11 , 12 ], and the easy recombination of photogenerated electron–hole pairs [ 11 ]. Additionally, some risks are associated with the application of this nanomaterial due to the possible presence of residual nanoparticles in treated waters and their difficult separation, which involves additional purification steps, such as chemical and physical filtration, distillation, and reverse osmosis [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%